Cutaneous mucormycosis in systemic lupus erythematosus: a case report - Li, Shiyang; Meng, Ting; Lin, Yuqiu; Xie, Dong; Li, Zhihua; Jiang, Qing (Frontiers in Immunology, 2025)
Mucormycosis is a life-threatening angioinvasive fungal infection caused by the Mucorales acidophilic fungi. In the article we report a case of cutaneous mucosporidiosis caused by infection with Rhizopus arrhizus in a patient with systemic lupus erythematosus (SLE). We analyze the causes of infection and death and concluded that cutaneous mucormycosis is a severe and refractory infection that has higher mortality in immunocompromised individuals or those with immune dysfunction. Early diagnosis and proactive treatment are paramount for a favorable prognosis.